(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Dentatorubral pallidoluysian atrophy (DRPLA) is a rare type of an autosomal dominant progressive late onset cerebellar ataxia. It is caused by a defect in a gene [CAG repeat in atrophin-1 (ATN1) on chromosome 12] and results in damage to the cerebellum, and to its connections within the central nervous system. It is also known as Haw River Syndrome and Naito-Oyanagi disease. This disorder seems to be very rare except in Japan. Patients with DRPLA can exhibit a variety of psychiatric symptoms in addition to extrapyramidal and cerebellar symptoms. We report a case who was 28 years old unmarried man presented at BSMMU, Dhaka in 2010. The present work highlights the variable mode of presentation of DRPLA and the difficulty of an early diagnosis without facility of genetic analysis. The aim of our report was to describe typical clinical presentations of the disease without positive family history. Our patient presented with unsteadiness during walking, irrelevant behavior and talking, incontinence of urine and stool with occasional myoclonic seizure and dementia. DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11367 J Bangladesh Coll Phys Surg 2012; 30: 48-52